Pericarpial nectary-visiting ants do not provide fruit protection against pre-dispersal seed predators regardless of ant species composition and resource availability - Andre Sanz-Veiga, Priscila (2017)
Fil: Andre Sanz-Veiga, Priscila. Universidade Estadual Paulista. Instituto de Biociências. Laboratório de ecologia de polinização e interação; Brasil.